Embracing the new norm in teaching and learning via G suite for education: a multidimensional perspective / Gurnam Kaur Sidhu ... [et al.] - Sidhu, Gurnam Kaur; Khor Wei Chen, Melanie; Shamida, Arieff; Chan, Shao Wen (Universiti Teknologi MARA, 2022)
The Covid-19 global pandemic witnessed a paradigm shift where remote teaching and learning had to be embraced by both teachers and students alike at all education levels. The overnight rapid transition witnessed the employment of several online tools including G Suite for Education, launched by Google in 2006. Today, educational institutions all around the globe have embraced G Suite tools but one question that raises concern is its potential as a teaching and learning tool in today’s 21 st century remote learning classrooms. Therefore, this paper puts forward the findings of an exploratory study that investigated a multidimensional perspective involving both pre-service teachers and lecturers’ perspectives of G Suite for Education based on four dimensions of the Technology Acceptance Model (TAM), namely perceived usefulness, perceived ease of use, behavioural intention to use and actual system use. The study was set in a private university in Malaysia involving 50 preservice teachers and four lecturers. The study employed a sequential explanatory mixed methods research design wherein data were collected via a three-pronged approach involving the use of a test, a questionnaire, and semi-structured interviews. Quantitative data analysis involved both descriptive and inferential statistics whilst qualitative data were thematically analysed. Initial findings indicated that pre-service teachers’ knowledge of G Suite for Education is at the moderate level with both students and lecturers’ having positive perceptions of G Suite based on the four dimensions of TAM. Despite a few issues of concern and challenges, the findings also implied the potential of G Suite for Education as a viable tool in today’s new norm of remote teaching and learning.